THE ADVANTAGES AND DISADVANTAGES OF THINK-PAIR SHARE AND JIGSAW IN TEACHING WRITING SKILL - Nurlaila Tuanany (IAKN Ambon, 2019)
Writing is a difficult activity for second language learners. Many students in senior high school are struggling with the subject of English especially when it deals with writing in English. The learners who have little experience in writing will stuck in conveying their ideas. So, the students feel confused when the teacher asked them to write. This paper discusses the advantages and disadvantages of Think-Pair Share and Jigsaw in teaching writing skill. There are some disadvantages of using TPS. TPS can improve attendance and also reduce dropout rates. On the other hand, the use of TPS is time consuming. It also can be very noisy because the students work in group. In addition, jigsaw tehcnique proposes some advantages and disadvantages as well. It can develop cooperative behavior, establishing a better relationship among the students, develop academic skills of students, and students are able to learn more from their friends. Meanwhile, disadvantges of this technique are the speaker usually dominated by smart students and some students cannot accept the other students from different groups because usually students just want to be with their close friend.